Effect of Fe (III) on Pseudokirchneriella subcapitata at circumneutral pH in standard laboratory tests is explained by nutrient sequestration. (24th October 2016) - Arbildua, Jose J.; Villavicencio, German; Urrestarazu, Paola; Opazo, Margaret; Brix, Kevin V.; Adams, William J.; Rodriguez, Patricio H.
Abstract: The complex chemistry of iron (Fe) at circumneutral pH in oxygenated waters and the poor correlation between ecotoxicity results in laboratory and natural waters have led to regulatory approaches for iron based on field studies (US Environmental Protection Agency Water Quality Criteria and European Union Water Framework Directive proposal for Fe). The results of the present study account for the observed differences between laboratory and field observations for Fe toxicity to algae ( Pseudokirchneriella subcapitata ). Results from standard 72‐h assays with Fe at pH 6.3 and pH 8 resulted in similar toxicity values measured as algal biomass, with 50% effect concentrations (EC50) of 3.28 mg/L and 4.95 mg/L total Fe(III), respectively. At the end of the 72‐h exposure, however, dissolved Fe concentrations were lower than 30 μg/L for all test concentrations, making a direct toxic effect of dissolved iron on algae unlikely. Analysis of nutrient concentrations in the artificial test media detected phosphorus depletion in a dose‐dependent manner that correlated well with algal toxicity. Subsequent experiments adding excess phosphorus after Fe precipitation eliminated the toxicity. These results strongly suggest that observed Fe(III) toxicity on algae in laboratory conditions is a secondary effect of phosphorous depletion. Environ Toxicol Chem 2017;36:952–958. © 2016 SETAC